The influence of service quality and customer review on purchasing decisions (Study Case of Shopee Marketplace) - Rubiatna Hardja; I Dewa Gede Sayang Adi Yadnya (Jurnal Mantik, 2023)
The ease of internet access has changed people's shopping behavior, from shopping directly to the store (Offline) to online at the marketplace. This change in behavior also affects consumer buying decisions. In addition, the inconsistency in the results of research conducted by previous researchers on purchasing decisions is the background of this thesis with the aim of answering the formulation of problems regarding the effect of service quality and customer reviews on purchasing decisions in the shopee marketplace. The method used in this research is quantitative method. The technique used for sampling Purposive sampling, because the population is unknown, using the Rao Purba Formula with a sample of 97 respondents. Data was collected through distributing questionnaires online using google form. The results showed that service quality and customer review partially had a positive effect on purchasing decisions. And the results show that service quality and customer review have a significant effect simultaneously or together on purchasing decisions.